The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15376/biores.16.2.2774-2788
|View full text |Cite
|
Sign up to set email alerts
|

Printability and properties of 3D-printed poplar fiber/polylactic acid biocomposite

Abstract: To efficiently and economically utilize a wood-plastic biocomposite, an eco-friendly biocomposite was prepared using modified poplar fiber and polylactic acid (PLA) via 3D printing technology for the first time. First, the effects of poplar fiber (0, 1, 3, 5, 7, and 9%) on the mechanical and rheological properties of the printed biocomposites were investigated. Subsequently, the printing parameters, including printing temperature, speed, and layer thickness, were optimized to obtain the biocomposite with super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The flexural strength decreased with the addition of wood flour to the neat PLA polymer. Similarly, it was indicated that the flexural strength decreased as a result of adding wood flour/plant fiber to PLA polymer (Narlıoğlu et al 2021;Yang et al 2021). It was reported that the flexural strength decreases with the addition of kenaf fiber to neat PLA and this decrease is due to the poor adhesion between kenaf fibers and PLA (Huda et al 2008).…”
Section: Fig 3 Tensile Strength and Modulus Of 3d-printed Samplesmentioning
confidence: 96%
“…The flexural strength decreased with the addition of wood flour to the neat PLA polymer. Similarly, it was indicated that the flexural strength decreased as a result of adding wood flour/plant fiber to PLA polymer (Narlıoğlu et al 2021;Yang et al 2021). It was reported that the flexural strength decreases with the addition of kenaf fiber to neat PLA and this decrease is due to the poor adhesion between kenaf fibers and PLA (Huda et al 2008).…”
Section: Fig 3 Tensile Strength and Modulus Of 3d-printed Samplesmentioning
confidence: 96%
“…One promising root to make PLA suitable for 3D printing is to add natural fillers to the polymers, such as calcined shell particles (CSh), straw meal, and poplar fibers. The resulting materials are completely biodegradable and result in a higher tensile strength of the polymers [66][67][68]. Copper and lignin are used as fillers for impact resistance enhancements.…”
Section: Polylactic Acid Applicationsmentioning
confidence: 99%
“…Thus, they increased with the decrease of layer height. As the layer height decreases, the density of the specimen increases, the more the polymeric substance and crystalline aggregates inside it are dispersed, and the more the refractive index of light propagating inside the material fluctuates (Yang et al 2022). Therefore the scattering of light increases, the uniformity of light output increases, and the haze increases.…”
Section: Effect Of Layer Height On Light Transmittance and Hazementioning
confidence: 99%